Energy–Environment–Industry Intersection: Rural and Urban Inequity and Approach to Just Transition - Li Sun; Sitong Wang; Jinqiu Wang (Land, 2025)
The intersection of energy, environment, and industry presents distinct challenges and opportunities in rural and urban settings, highlighting disparities in access, impact, and policy effectiveness. This paper examines the systemic inequities between rural and urban regions in the transition to a sustainable energy future. It explores how policies and technologies can promote a just transition that ensures equitable economic development, environmental protection, and energy access for all communities. The key findings reveal that the average urban environmental pollution has transitioned from 10.1574 in 2007 to 8.9540 in 2022, indicating an improvement over time. From 2007 to 2022, the average level of rural environmental pollution has transitioned from 15.1123 in 2007 to 14.2675 in 2022, suggesting an improvement in performance over the specified timeframe. This shows that rural environmental pollution (14.8442) is more serious than urban environmental pollution (9.0892), even though rural environmental pollution is constantly improving. Regarding driving factors affecting urban and rural environmental pollution, we illustrate that energy consumption and environmental protection investment are important factors through which environmental regulation influences urban environmental pollution, while only environmental protection investment is an important factor through which environmental regulation influences rural environmental pollution. The findings suggest that only in the western region do stronger environmental regulations significantly reduce urban pollution, while strengthening environmental regulations improves rural pollution across all three regions, with the most pronounced effect in the west. By integrating quantitative and policy analysis, the study proposes inclusive strategies that balance economic resilience, social justice, and environmental sustainability, fostering a fair transition toward a low-carbon future.